Deflection Laws of Gas Drainage Boreholes in Interbedded Soft and Hard Seams: A Case Study at Xinzheng Coal Mine, China - Xiaoyan Sun; Zhiheng Cheng; Liang Chen; Zhenhua Li; Hongbing Wang; Shuaifeng Yin (Advances in Civil Engineering)
Coal and gas outbursts can lead to serious disasters in coal mines. The drilling of boreholes to predrain the gas is an effective measure for preventing such accidents. However, due to the complexity of the geological situation, the drilling trajectory often deviates from the design trajectory, resulting in poor gas extraction. To solve the problem of gas drainage borehole deflection, an analytic hierarchy process (AHP) model is established based on geological factors, technical factors, and human factors. The AHP model is used to rank the weights of various influencing factors, and the analysis is combined with a drilling model and engineering examples. Finally, the results show that soft and hard interlayers are the most important factors affecting the deflection of the borehole. The rock drilling model is mainly affected by the formation forces. The regularity of the change in the azimuth angle during drilling is not obvious when the angle of the encountered layer is less than some critical value. When the borehole is skewed downward, the deflection angle ranges from 0 to 4°, and the deflection of the borehole occurs mainly at the interface of the rock layers. When the angle of the encountered layer is greater than the critical value, the borehole is skewed upward, with a deflection angle of 0–6°, and the deflection occurs at the rock interface. The trajectory curve obtained by theoretical predictions from field data is found to be consistent with that of an actual project.